Analysis of morphological characteristics and expression levels of extracellular matrix proteins in skin wounds to determine wound age in living subjects in forensic medicine. (January 2015) - Fronczek, Judith; Lulf, Ronald; Ibrahim Korkmaz, H.; Witte, Birgit I.; van de Goot, Franklin R.W.; Begieneman, Mark P.V.; Krijnen, Paul A.J.; Rozendaal, Lawrence; Niessen, Hans W.M.; Reijnders, Udo J.L.
Highlights: A new method to determine wound age in living subjects. Morphological characteristics in wound age determination in living subjects. Extracellular matrix proteins in wound age determination in living subjects. The introduction of a probability scoring system for wound age estimation in living subjects. Abstract: Objective: Wound age determination in living subjects is important in routine diagnostics in forensic medicine. Macroscopical description of a wound to determine wound age however is inadequate. The aim of this study was to assess whether it would be feasible to determine wound age via analysis of morphological characteristics and extracellular matrix proteins in skin biopsies of living subjects referred to a forensic outpatient clinic. Methods: Skin biopsies ( n = 101), representing the border area of the wound, were taken from skin injuries of known wound age (range: 4.5 h–25 days) in living subjects. All biopsies were analyzed for 3 morphological features (ulceration, parakeratosis and hemorrhage) and 3 extracellular matrix markers (collagen III, collagen IV and α-SMA). For quantification, biopsies were subdivided in 4 different timeframes: 0.2–2 days, 2–4 days, 4–10 days and 10–25 days old wounds. Subsequently, a probability scoring system was developed. Results: For hemorrhage, collagen III, collagen IV and α-SMA expression no relation with wound age was found. Ulceration was only found in wounds of 0.2–2, 2–4 and 4–10 days old, implying that the probability that a wound was more than 10 days old in case of ulceration is equal to 0%. Also parakeratosis was almost exclusively found in wounds of 0.2–2, 2–4 and 4–10 days old, except for one case with a wound age of 15 days old. The probability scoring system of all analyzed markers, as depicted above, however can be used to calculate individual wound age probabilities in biopsies of skin wounds of living subjects. Conclusions: We have developed a probability scoring system, analysing morphological characteristics and extracellular matrix proteins in superficial skin biopsies of wounds in living subjects that can be applied in forensic medicine for wound age determination.